Skrining Kesehatan Dasar pada Guru SD dan SMP SIT Bina Insan Parepare sebagai Upaya Deteksi Dini Faktor Risiko Penyakit Tidak Menular - Nurul Mutiah Aminuddin; Nurul Mufidah Damry; Rayhani Ichsan; Dewi Yusuf; Muhammad Ichsan Ali; Amir Hamzah Basir (Universitas Negeri Makassar, 2026)
Abstract. Non-communicable diseases (NCDs), such as hypertension, diabetes mellitus, obesity, and cardiovascular disease, are major causes of global morbidity and mortality. Risk factors for NCDs often develop gradually and remain undetected during productive age, including among educators who have high levels of activity and workload. Teachers are a strategic group that plays an important role in building a healthy lifestyle culture within the school environment, yet they often receive limited attention in preventive health screening programs. This community service activity aimed to conduct basic health screening among elementary and junior high school teachers at SIT Bina Insan Parepare as an effort to support early detection of NCD risk factors. The activity was carried out through the measurement of blood pressure, body mass index (BMI), waist circumference, random blood glucose levels, and health education on NCD prevention and healthy lifestyle practices. The activity also included brief consultations related to the participants’ examination results and health risk factors. The results showed that some participants had NCD risk factors, including elevated blood pressure, overweight/obesity, increased waist circumference, and random blood glucose levels above the normal range. In addition, participants showed high enthusiasm toward the health screening and education provided. This activity was beneficial in increasing teachers’ awareness of the importance of regular health checks and the adoption of healthy lifestyle behaviors as part of promotive and preventive efforts against non-communicable diseases.Keywords: health screening; non-communicable diseases; teachers; early detection; promotive and preventive; healthy aging